Step length synergy while crossing obstacles is weaker in patients with Parkinson's disease - Ambike, Satyajit; Penedo, Tiago [UNESP]; Kulkarni, Ashwini; Santinelli, Felipe Balistieri [UNESP]; Barbieri, Fabio A. [UNESP] (Elsevier, 2021)
Background: Impaired movement stability is a common symptom of Parkinson's disease (PD) that leads to falls and mishandled objects. Decline in synergistic stabilization of movement in PD patients has been observed in manual and postural tasks. However, locomotor synergies have not been quantified in PD patients. Research question: The purpose of this work was to quantify the strength of the synergy stabilizing the step length while crossing an obstacle in PD patients. We hypothesized that (1) the distances of the front and rear feet relative to the obstacle would display compensatory across-trial co-variance that stabilizes step length in PD patients and age-matched controls, and (2) the step-length stabilization would be weaker in PD patients. Methods: Thirteen PD patients and eleven healthy age-matched controls walked up to and stepped over a 15 cm high obstacle fifteen times.We measured the distances of the rear and front foot toes from the obstacle during the crossing step. We used the uncontrolled manifold method to parse the across-trial variance in toe distances into a component that maintains the step length and a component that changes the step length. These variance components yielded the synergy index that quantified the stability of step length. Results: Step length was stabilized in PD patients as well as controls. However, the synergy index was 53% lower in the PD patients (p < 0.01). Thus, both our hypotheses were supported. Significance: This is the first study reporting impaired locomotor synergies in PD patients. Most PD patients in our sample were early stage (10 out of 13 patients were Hoehn-Yahr ≤ 2). Therefore, this result motivates further studies to establish step-length synergy during adaptive locomotor tasks as a biomarker for early detection of locomotor impairments in PD patients.
Keywords: Adaptive gait; Gait stability; Uncontrolled manifold analysis